Optimization of Adsorption of Eugenol-Silica Gel Composites to Metal Ions Cu (II) Using Box Behnken Method - Fitra Rachmalia; Muhammad Fathurrahman; Sutanto Sutanto (Universitas Pakuan, 2022)
Silica gel can be used as an absorbent so that it can also be used as a process for making eugenol-silica gel composites. This study aims to optimize the adsorption of the eugenol-silica gel composite to Cu (II) metal ions and to determine the maximum absorption capacity and adsorption constant of the Langmuir and Freundlich isotherm model. This research begins with determining the optimization of contact time 10-60 minutes, temperature 20-45 oC and the weight of the adsorbent is carried out in the range of 0.10-0.20 grams in a 50 mL solution and the experimental design of the box Behnken method will determine three variables through (Response Surface Methodology). Furthermore, the determination of Cu levels by preparing 100 ppm Cu mother liquor, making a standard series, and testing with Atomic Absorption Spectroscopy (AAS), and then determination of Langmuir and Freundlich adsorption isotherms. The results showed that the optimum conditions for the adsorption process using Response Surface Methodology (RSM) were at a contact time of 30 minutes, a temperature of 45 oC with an adsorbent weight of 0.10 grams in a 50 mL solution, in Langmuir and Freundlich isothermal adsorption. The adsorption process takes place in two directions (reversible) the values of Kf, b and n are 8331; -5.2224 and -0.4541. The adsorption process takes place in two directions (reversible) the values of Kf, b and n are 8331; -5.2224 and -0.4541. The adsorption process takes place in two directions (reversible) the values of Kf, b and n are 8331; -5.2224 and -0.4541.